NTR1 is involved in heat stress tolerance through mediating expression regulation and alternative splicing of heat stress genes in Arabidopsis - He, Lei; Wu, Qi; Jin, Ye; Fan, Ye; Shi, Huazhong; Wang, Yizhong; Yang, Wannian (Frontiers in Plant Science, 2023)
As a common adverse environmental factor, heat stress (HS) drastically changes the plant transcriptome not only at the transcription level, but also increasing alternative splice (AS), especially intron retention (IR) events. However, the exact mechanisms are not yet well understood. Here we reported that NTC-Related protein 1 (NTR1), which acts as an accessory component for spliceosome disassembly, is necessary for this process. The mutants of NTR1, both the T-DNA insertion and the point mutation identified through ethyl methanesulfonate (EMS) mutagenesis screening, are vulnerable to HS, indicating NTR1 is essential for plant HS tolerance. At the molecular level, genes of response to heat and response to temperature stimulus are highly enriched among that of heat-induced but less expressed in the ntr1 mutants. Besides, a large portion of HS response (HSR) genes such as heat shock transcription factors (HSFs) and heat shock proteins (HSPs) are less induced by heat treatment and more AS especially IR events were found in heat-treated ntr1 mutants. Furthermore, HS suppressed the expression of NTR1 and NTR1-associated complex components. Thus, it is very likely that upon HS plant reduces the expression of the NTR1-associated complex to fulfill the fast demands for transcription of HSR genes such as HSFs and HSPs, which in turn results in the accumulation of improper spliced especially IR products and eventually causes harm to plants.